Beyond the curse policies to harness the power of natural resources - Arezki, Rabah; Gylfason, Thorvaldur 1951-; Sy, Amadou N. R. (International Monetary Fund, 2011)
Countries with an abundance of natural resources, many of which are in sub-Saharan Africa, often show a record of relatively poor economic performance compared with non-resource-rich countries. The chapters in this volume explore the potential challenges to countries with abundant natural resources and ways to manage these challenges so as to reap the benefits of resource wealth while avoiding the pitfalls. The book is divided into five sections, which explore commodity markets and the macroeconomy, economic diversification and the role of finance, fiscal policy, exchange rates and financial stability, and governance. The ideas in this book were first presented at a seminar in November 2010 that was aimed primarily at policymakers in sub-Saharan Africa and brought together ministers, central bank governors, other senior policymakers, and well-known academics.